Isolamento e caracterização da tripsina do ceco pilórico da espécie Scomberomorus brasiliensis (Serra) - Souza , Cledson Barros de (2018)
Scomberomorus brasiliensis, popularly known as serra in Brazil, is a saltwater carnivorous fish found in the coastal zone along the entire American continent. It is a very consumed animal in Brazil, with high socioeconomic value for the state of Alagoas. Trypsins are proteolytic molecules that are important in the digestion of various organisms and are already used in different areas of industry, such as the textile, food and pharmacological sectors, as well as being widely used in different areas of scientific research. There is the possibility of extracting important biological molecules such as the trypsins produced in the viscera that are discarded from the animal and which can be applied industrially, which gives usefulness to the residues and contributes to the reduction of pollution, since up to 30% of the weight of these animals is composed of residues. The extracts from four different viscera, liver, pyloric cecum, posterior and anterior intestine were prepared, and a higher presence of trypsin was detected in the pyloric cecum, an extract from which the isolation process was started, composed of saline fractionation and chromatography by molecular exclusion. The 20-40% fraction of the precipitation was applied to a column with sephacryl S-100 resin and the chromatography fractions listed 15 to 19 showed activity for trypsin and the purity of the enzyme was confirmed by SDS-PAGE, having approximate molecular mass of 26 kDa. The isolated trypsin was characterized by optimum temperature and thermal stability curves in the range of 30 to 70 ° C, optimum pH and pH stability in the range of 4.0 to 10.0, enzymatic kinetics curve with substrate concentrations 0.016 to 6 mM and inhibition tests with PMSF, Benzamidine, 2-mercaptoethanol and EDTA. It was possible to extract an enzyme of biotechnological importance of residues with no commercial value, to isolate and characterize it with success, being necessary to identify applications for the same.